THE APPLICATION OF INDIVIDUAL COUNSELING USING COGNITIVE RESTRUCTURING TECHNIQUES TO REDUCE STRESS IN CLIENT T, WHO IS PREGNANT OUT OF WEDLOCK - Amy Chintiea; Suryati Suryati; Hartika Utami Fitri (Jurnal Konseling Pendidikan Islam, 2025)
This research is entitled "Application of Individual Counseling with Cognitive Restructuring Techniques to Reduce Stress in Clients Who Are Pregnant Out of Wedlock". The background of this research is stress. Stress is defined as the inability to overcome threats faced by humans mentally, physically, emotionally and spiritually, which at some point can affect the human's physical condition. Therefore, providing individual counseling using cognitive restructuring techniques will be very effective in reducing the stress experienced by clients.  This research aims to determine individual counseling using cognitive restructuring techniques to reduce stress in T clients who are pregnant out of wedlock. This research uses a qualitative approach with a case study type of research. Data collection tools include interviews, observation and documentation. Meanwhile, data analysis techniques are data collection, data reduction, data presentation, and conclusions. The subject of this research was 1 teenage girl aged 15 years. The results of this research show that after carrying out the individual counseling process in 4 meetings using cognitive restructuring techniques, it can reduce the stress experienced by client T who is pregnant out of wedlock. The stages of individual counseling using cognitive restructuring techniques in reducing stress in T clients who are pregnant out of wedlock are using the initial stage, transition stage, activity stage and final stage.